2012
DOI: 10.1080/19440049.2012.691556
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic determination of norbixin and tartrazine in sugar

Abstract: In this paper, a method for the detection of norbixin and tartrazine in sugar by means of resonance Raman spectroscopy is presented. The extraction was done in four steps using methanol and the measurements were performed in aqueous solution. The excitation wavelength was 514 nm for norbixin and 488 nm for tartrazine samples. The characteristic resonance Raman signals of the dyes were fitted by different functions. Depending on the R² values of the different fits, each spectrum was classified as positive or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…As for the morphology of the newly formed bone tissue in this study (Figure 6), the SEM micrography revealed that the membrane group after 15 days had already developed a new bone matrix filling the area of the induced defect, with quality of neoformed bone tissue in 30 days superior to the control, showing biocompatibility, osteoconductivity, and osteogenesis throughout the experiment, corroborating with the other results found. Sousa et al 26 physicochemically characterized the PHB/norbixin membrane and revealed characteristics similar to those found in Figure 8e, just as Figure 7 confirmed the presence of peaks similar to those of the membrane inside the induced bone defect, [35][36][37][38] suggesting their presence and adherence to the inside of the lesion site throughout the entire observational period.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As for the morphology of the newly formed bone tissue in this study (Figure 6), the SEM micrography revealed that the membrane group after 15 days had already developed a new bone matrix filling the area of the induced defect, with quality of neoformed bone tissue in 30 days superior to the control, showing biocompatibility, osteoconductivity, and osteogenesis throughout the experiment, corroborating with the other results found. Sousa et al 26 physicochemically characterized the PHB/norbixin membrane and revealed characteristics similar to those found in Figure 8e, just as Figure 7 confirmed the presence of peaks similar to those of the membrane inside the induced bone defect, [35][36][37][38] suggesting their presence and adherence to the inside of the lesion site throughout the entire observational period.…”
Section: Discussionsupporting
confidence: 57%
“…The biomembrane promoted the filling of the bone defect and served as a scaffold for the migration of osteoprogenitor cells because it is biocompatible, resorbable, and osteoconductive, as its adhesion was detected inside the bone defect induced in Figure 6d, in which it was observed that the biomaterial it was probably present on the surface of the filled defect, in view of the physico-chemical characterization shown in Figure 9 which identified Raman peaks representative of the components of the biomaterial in accordance with the literature. [35][36][37][38] For Alves et al, 9 the peak increase ~960 cm À1 can be correlated to high bone mineral density, as well as to its maturation.…”
Section: Discussionmentioning
confidence: 98%
“…These effects make knowledge about food components an important issue for the detection of and information on the synthetic colorants in foodstuffs and beverages. Towards developing this knowledge, many analytical methods have been developed using spectrometric determination (Blanco, Campana, & Barrero, 1996;El-Sheikh & Al-Degs, 2013;Ni, Qi, & Kokot, 2001;Santos, Demiate, & Nagata, 2010), Raman spectroscopic (Uhlemanna et al, 2012), voltammetry (Gan, Sun, Meng, Song, & Zhang, 2013;Ghoreishi et al, 2012;Ni, Bai, & Jin, 1997), capillary electrophoresis (Huang, Chiu, Sue, & Cheng, 2003;López-Montes, Dupont, Desmazières, & Lavédrine, 2013;Prado, Boas, Bronze, & Godoy, 2006), and high performance liquid chromatography with diode array detection (HPLC-DAD) (Kirschbaum, Krause, Pfalzgraf, & Bruckner, 2003) for synthetic colorant determination in foodstuffs and beverages. These techniques require prior sample preparation and can be used anywhere from a simple dilution followed by filtration up to more advanced techniques such as solid phase extraction (SPE) through centrifugation and sonication of samples to extract all the colorant.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that another phenomenon, the Resonant Raman Spectroscopy, might be exploited to enhance the signal of an organic molecule present in very low concentration . This effect can be adequately used for analysis of complex matrices; it is based on the Raman excitation of the sample using a wavelength which occurs within the electronic absorption band.…”
Section: Introductionmentioning
confidence: 99%